Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1016/s0006-3495(03)74618-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Modes of Peptides and Globular Proteins in Solution Observed by Ultrafast OHD-RIKES Spectroscopy

Abstract: The low-frequency (1-200 cm(-1)) vibrational spectra of peptides and proteins in solution have been investigated with ultrafast optical heterodyne-detected Raman-induced Kerr-effect spectroscopy (OHD-RIKES). Spectra have been obtained for di-L-alanine (ALA(2)) and the alpha-helical peptide poly-L-alanine (PLA) in dichloroacetic acid solution. The poly-L-alanine spectrum shows extra amplitude compared to the di-L-alanine spectrum, which can be explained by the secondary structure of the former. The globular pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
147
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 48 publications
(67 reference statements)
26
147
0
Order By: Relevance
“…Although uncovered computationally, this mode was not expected to contribute significantly to the experimental IR absorption spectrum of liquid water under normal conditions, but was conjectured to be enhanced through solute-induced modifications within the liquid water solvation shell. Additionally an 80 cm −1 mode has been reported in Raman-induced Kerr-effect spectroscopy measurements on globular proteins [39]. In this case, the 80 cm −1 mode has been attributed to fluctuations taking place within the protein secondary structure.…”
Section: Protein Interactions and Potential Energy Barrier Transitionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Although uncovered computationally, this mode was not expected to contribute significantly to the experimental IR absorption spectrum of liquid water under normal conditions, but was conjectured to be enhanced through solute-induced modifications within the liquid water solvation shell. Additionally an 80 cm −1 mode has been reported in Raman-induced Kerr-effect spectroscopy measurements on globular proteins [39]. In this case, the 80 cm −1 mode has been attributed to fluctuations taking place within the protein secondary structure.…”
Section: Protein Interactions and Potential Energy Barrier Transitionsmentioning
confidence: 83%
“…Correspondingly, it is possible that the increase in intensity at ∼20 cm −1 in the protein-ligand sample also reflects localized protein, intramolecular interactions that accompany ligand binding. The 20 cm −1 experimental mode may be associated with delocalized side-chain fluctuations and has been uncovered in numerous protein investigations [37][38][39].…”
Section: Hinge-bending Mode and Protein Intramolecular Interactionsmentioning
confidence: 92%
“…The experimental setup for the OKE measurements has been described previously [16,[69][70][71][72] and uses 800-nm 24-fs (FWHM) sech 2 pulses with 8 nJ per pulse at a repetition rate of 76 MHz. The beam is split into pump and probe beams (9:1), which are co-focused by a 10-cm focal length achromat into the sample contained in a 2-mm-pathlength quartz cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…Generally it is found that these modes can be satisfactorily fit by the Brownian (dampedharmonic) oscillator function [16,23] …”
Section: Interpretation Of the Intermolecular Spectrummentioning
confidence: 98%
“…The full DR spectrum is reconstructed by patching using the Kramers-Kronig transform. OKE measures the <α xy α xy (t)> correlation function of the anisotropic part of the polarisability tensor directly in the time domain [17,[21][22][23][24]. In our set-up using a laser producing 20-fs pulses, delays from 10 fs to 4 ns can be achieved corresponding to the effective frequency range 250 MHz to ~50 THz.…”
Section: Introductionmentioning
confidence: 99%